Perlindungan Terhadap Kezaliman Kepada Anak Yang Terdapat Pada Sekolah (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Acts of violence against children in schools deserve the attention of the Indonesian Child Welfare Commission. The current situation creates a context that needs further attention for legal defense in which children are targets of cruelty in schools, as everyone knows that educational institutions are a place where the young generation is educated to become educated adults for the next generation. The role of the teacher is as a parent at school, sharing good and correct knowledge and enlightenment, not being used as a bully to students at school. The main issue discussed first is what factors cause the many incidents of injustice towards the younger generation in educational institutions in Indonesia at this time and the steps taken by KPAI towards children in Indonesia as they exist. In the article, the method of study used is theoretical study by applying the document collection method, namely library research or book study. It is hoped that the results of this study will invite elements including teachers, parents and students to involve schools in monitoring their students and taking part in the role that educational institutions can use to provide an umbrella for their students when carrying out the role of teachers as moral shapers. Teachers who are devoted to the Creator, share the most important encouragement and passion with parents at home to teach children to think positively about the injustice that befalls them.